2007
DOI: 10.1016/j.physbeh.2007.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Obesity by choice revisited: Effects of food availability, flavor variety and nutrient composition on energy intake

Abstract: Recent work suggested that the energy intake and weight gain of rats maintained on chow and 32% sucrose solution could be increased by simply offering more sources of sucrose (Tordoff, 2002). In Experiment 1 this procedure was replicated but the effect was not: rats given one bottle of sucrose and five bottles of water consumed as much sucrose as those given five bottles of sucrose and one of water. Adding different flavors to the sucrose did not increase intakes further in Experiment 2. The relative potency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
2
15
1
Order By: Relevance
“…In this study, our goal was not to study diet and obesity, even though relative to typical laboratory chows, the diet we chose has a slightly higher energy density (15.9 vs. ~13 kJ/g) and more carbohydrate (68% vs. ~59% of total energy) from sucrose compared with laboratory chow. Based on comparisons made in mice [45], the AIN-76A diet appears to be more “obesigenic” than chow but not nearly as much as the high fat diets typically used to produce obesity. Therefore our study does not specifically model dietary obesity, and the rats maintained a low-to-average proportion of body fat, e.g., less than 20% in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our goal was not to study diet and obesity, even though relative to typical laboratory chows, the diet we chose has a slightly higher energy density (15.9 vs. ~13 kJ/g) and more carbohydrate (68% vs. ~59% of total energy) from sucrose compared with laboratory chow. Based on comparisons made in mice [45], the AIN-76A diet appears to be more “obesigenic” than chow but not nearly as much as the high fat diets typically used to produce obesity. Therefore our study does not specifically model dietary obesity, and the rats maintained a low-to-average proportion of body fat, e.g., less than 20% in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…The liquid sucrose and chow and the chow, liquid sucrose, and fat groups consumed more energy than the chow and fat and the chow only groups. This coincided with the chow and liquid sucrose group having a similar body weight as the chow, liquid sucrose, and fat group but a higher body weight than the chow and fat and the chow only groups [14]. A similar model of diet induced weight gain has been associated with changes in hypothalamic neuropeptide expression and the development of glucose intolerance and insulin insensitivity [15, 16].…”
Section: 0 Introductionmentioning
confidence: 92%
“…When combined with chow, the physical form of sucrose and fat affect preference because rats consume more energy from sucrose when consumed in liquid form compared to solid, but consume more energy from fat in solid form compared to oil [11, 12]. Liquid sucrose has previously been shown to promote overeating in chow fed rats by Castonguay et al[13] and Ackroff and Sclafani [14] and lard by Ackroff and Sclafani [14]. The latter study found that a chow, 32% liquid sucrose solution, and fat (vegetable shortening) group did not increase energy intake compared to a chow and liquid sucrose group.…”
Section: 0 Introductionmentioning
confidence: 99%
“…However, it has also been postulated that presenting more of the same highly palatable food (such as five bottles of 32% sucrose) results in more overconsumption (139). This is, however, under debate, because others could not reproduce these findings (1).…”
Section: The Future With Animal Modelsmentioning
confidence: 99%